Oral fluconazole use in the first trimester and risk of congenital malformations: population based cohort study. (20th May 2020) - Zhu, Yanmin; Bateman, Brian T; Gray, Kathryn J; Hernandez-Diaz, Sonia; Mogun, Helen; Straub, Loreen; Huybrechts, Krista F
Abstract: Objective: To examine the risk of congenital malformations associated with exposure to oral fluconazole at commonly used doses in the first trimester of pregnancy for the treatment of vulvovaginal candidiasis. Design: Population based cohort study. Setting: A cohort of pregnancies publicly insured in the United States, with data from the nationwide Medicaid Analytic eXtract 2000-14. Participants: Pregnancies of women enrolled in Medicaid from three or more months before the last menstrual period to one month after delivery, and infants enrolled for three or more months after birth. Interventions: Use of fluconazole and topical azoles was established by requiring one or more prescriptions during the first trimester of pregnancy. Main outcome measures: Risk of musculoskeletal malformations, conotruncal malformations, and oral clefts (primary outcomes), associated with exposure to oral fluconazole, diagnosed during the first 90 days after delivery, were examined. Results: The study cohort of 1 969 954 pregnancies included 37 650 (1.9%) pregnancies exposed to oral fluconazole and 82 090 (4.2%) pregnancies exposed to topical azoles during the first trimester. The risk of musculoskeletal malformations was 52.1 (95% confidence interval 44.8 to 59.3) per 10 000 pregnancies exposed to fluconazole versus 37.3 (33.1 to 41.4) per 10 000 pregnancies exposed to topical azoles. The risks of conotruncal malformations were 9.6 (6.4 to 12.7) versus 8.3 (6.3 to 10.3) per 10 000 pregnancies exposed to fluconazole and topical azoles, respectively; risks of oral clefts were 9.3 (6.2 to 12.4) versus 10.6 (8.4 to 12.8) per 10 000 pregnancies, respectively. The adjusted relative risk after fine stratification of the propensity score was 1.30 (1.09 to 1.56) for musculoskeletal malformations, 1.04 (0.70 to 1.55) for conotruncal malformations, and 0.91 (0.61 to 1.35) for oral clefts overall. Based on cumulative doses of fluconazole, the adjusted relative risks for musculoskeletal malformations, conotruncal malformations, and oral clefts overall were 1.29 (1.05 to 1.58), 1.12 (0.71 to 1.77), and 0.88 (0.55 to 1.40) for 150 mg of fluconazole; 1.24 (0.93 to 1.66), 0.61 (0.26 to 1.39), and 1.08 (0.58 to 2.04) for more than 150 mg up to 450 mg of fluconazole; and 1.98 (1.23 to 3.17), 2.30 (0.93 to 5.65), and 0.94 (0.23 to 3.82) for more than 450 mg of fluconazole, respectively. Conclusions: Oral fluconazole use in the first trimester was not associated with oral clefts or conotruncal malformations, but an association with musculoskeletal malformations was found, corresponding to a small adjusted risk difference of about 12 incidents per 10 000 exposed pregnancies overall.